The Operational Framework of the Greek Educational System as an Obstacle to the Implementation of Sustainable School - Kougias, Konstantinos; Efstathopoulos, John (Frontiers in Education, 2020)
The introduction of sustainability education into the educational reality in recent decades to raise student’s awareness of environmental, social and cultural issues has gradually led to a change in the perception of school as an organization at all levels of its function. The traditional approach of school is receding and the concept of sustainable school is emerging, transforming school into a factor of change of attitudes and behaviors, into a major lever of transforming society toward sustainability, leading to the revision of leadership and organization views. In Greece, sustainable school is a utopian image in an ideal society. The efforts made are fragmented and incomplete, as the narrow legal framework which is determined by the state. A number of practices are strictly followed on issues that cover the whole spectrum of the educational process, such as the appointment of school principals, teacher placements, teaching instructions, funding and financial management of the school unit, limiting the margin of the school administration to achieve a sustainable use of the available resources in order to continuously develop and improve school as an educational organization. The Greek educational system, through the uniformity of laws in all its fields, inhibits the implementation of sustainable school by lifting cobblestones and obstacles that this article attempts to illuminate.